Effect of microwave assisted extraction (MAE) on the phenolic content (TPC) and total flavoniod content (TFC) of three Malaysian plants curcuma longa linn (daun kunyit), syzygium polyanthum (daun salam) and diplazium esculentum (daun pucuk paku) - Looi, Kah Shien (2015)
Total phenolic content and total flavonoidic content of six different extracts from the leaves of Syzgium polyanthum (daun samak), Curcuma longa (daun kunyit) and Diplazium esculentum (Daun pucuk paku) were estimated using spectrophotometric method. The phenolic content in 95 % confidential interval for S. polyanthum ranged from 94.67 mg GAE/g to 412.17 mg GAE/g whereas for C. longa and D. esculentum ranged 120 mg GAE/g to 520.50 mg GAE/g and 90.50 mg GAE/g to 427.17 mg GAE/g respectively. The flavonoidic content measured in 95% confidential interval for S. polyanthum ranged from 10.99 mg QE/g to 25.78 mg QE/g whereas for C. longa and D. esculentum ranged from 14.63 mg QE/g to 45.04 mg QE/g and 12.46 mg QE/g to 40.79 mg QE/g respectively. Ultimately, ethanolic extracts of all plant (leaves) samples showed the highest phenolic and flavonoid content exceptional for the D. esculentum in estimation of flavonoid content. Petroleum ether extracts do not readily dissolved in methanol due to its insoluble properties in polar solvent. Microwave assisted extraction in this study do showed a higher phenolic and flavonoid contents were obtained. There was a significant difference in the comparison between the solvents and the contents within these 3 plants samples (p < 0.05) for both total phenolic and flavonoidis content. The high content of phenolic and flavonoidic in the S. polyanthum, C. longa and D. esculetum could be promised on their benefits as antioxidant towards society.